Solar-driven proton and carbon dioxide reduction to fuels — lessons from metalloenzymes. (April 2015) - Bachmeier, Andreas; Armstrong, Fraser
Highlights: Artificial photosynthesis (AP) is one route to future renewable energy conversion. Fast and efficient redox enzymes are paradigm 'reversible' electrocatalysts for AP research. Metalloenzymes are attached to light-harvesting agents to give photo-electrocatalytic systems. New criteria for the catalytic performance of metal-containing active sites are revealed. Relay centres with low reorganisation energies trap photo-generated electrons. Abstract : Metalloenzymes such as hydrogenases and carbon monoxide dehydrogenase can be attached to light-harvesting agents to produce informative photocatalytic systems of varying intricacy. Systematic studies yield important insight into mechanistic and design principles of artificial photosynthesis – one route to future renewable energy conversion, and the unconventional experiments reveal interesting new criteria for the catalytic performance of metals in biology. Recent advances are interpreted in terms of the importance of enzyme active centres that have evolved to perform fast and efficient catalysis using abundant elements, along with the ability of enzymes to trap photo-generated electrons by virtue of having receding, buried relay centres with low reorganisation energies.